Metaheuristics Applied To the Intercity Public Transport Problem - Rodriguez, Diego Alejandro (2011)
This paper presents a study on the use of metaheuristics for the treatment of the NP-hard problem known as the Intercity Public Transport Problem. The study aimed at optimizing the bus routes and frequencies through two basically different techniques: Genetic Algorithms and Simulated Annealing. The complete implementation of the algorithms was carried out on MALLBA, where traffic simulation was performed with SUMO (Simulation for Urban MObility). The testing case was an intercity passenger line linking the Argentinian cities of Bahía Blanca and Punta Alta.